Pemberdayaan Ekonomi Masyarakat Petani Melalui Pemanfaatan Buah Kelapa sebagai Bahan Baku yang diolah Menjadi Produk Kue dan Aneka Cemilan - Lydia Surijani Tatura; Berni Idji; Niniek Pratiwi (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2021)
This program aims to develop village potential during the Covid-19 pandemic. In increasing coconut commodities' economic value, coconut fruits as raw materials are processed into a delicious and nutritious cake and snack products that have selling value. Coconut farmers and the community generally use coconut fruit in the form of copra and cooking oil. The production uses traditional tools and raw materials that are sold on the traditional markets. The program is held in Londoun Village, Popayato Timur District, Pohuwato RegencyThe method used in this program is counseling and training for the community. With the flow of activities, namely preparation and debriefing of KKN students, then continued with implementation, namely counseling and training for the community. With community participation, it is expected to generate new ideas in processing coconut fruit for the sustainability of this program.